The effectiveness of early rehabilitation in patients with facial palsy - Runcheva, K. A. (Запорізький державний медичний університет, 2021)
Facial palsy (FP) is one of the most common pathology of the cranial nerves. FP causes high medical and social maladaptation and disorders of the psycho-emotional sphere. Objective. To evaluate the effectiveness of complex therapeutic measures on the dynamics of recovery processes in patients with facial nerve neuropathy depending on the date of onset of rehabilitation.
Keywords: тези